Hydrogeology of an arid region : the Arabian Gulf and adjoining areas - Alsharhan, A. S. (Elsevier, 2001)
This book provides comprehensive information about the water resources of the Arabian Gulf region, an area that is symbolic as an arid to extremely arid belt. Filling an information gap it provides in-depth analyses of both natural and human-related constraints on water resources, and presents a new vision on efficient management of available water resources. It contains an overview of the physical geography and climatic constraints on water resources, systematic inventory of available traditional and non-traditional water resources, water-related problems, water conservation and legislations, comprehensive water laws applicable to the region, and modern techniques of water resources investigation. This work meets the needs of scientists, environmentalists, engineers, planners and decision makers. Senior undergraduate, graduate students and researchers of the Gulf area, and more generally of arid regions, will also find this volume valuable.